2015
DOI: 10.1002/hbm.22792
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity of brain regions related to visual word recognition: An fMRI study of Chinese reading

Abstract: Past neuroimaging studies have focused on identifying specialized functional brain systems for processing different components of reading, such as orthography, phonology, and semantics. More recently, a few experiments have been performed to look into the integration and interaction of distributed neural systems for visual word recognition, suggesting that lexical processing in alphabetic languages involves both ventral and dorsal neural pathways originating from the visual cortex. In the present functional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…Interest in modeling inter-regional connectivity has driven the development of new statistical techniques, as well as the application of established techniques from other fields [15*], including structural equation modeling, partial least squares, psychophysiological interactions and dynamic causal modeling. These techniques have demonstrated that functional interactions among brain areas are involved in a wide range of cognitive domains and correlate with performance, including cognitive control [16, 17], learning [18*], memory [19], attention [20], reward processing [21] and language [22]. Connectivity-based biofeedback studies have demonstrated that participants can be trained to self-regulate specific functional connections, resulting in desirable behavioral changes, such as increased subjective emotional valence ratings [23].…”
Section: From Regional Activations To Connectivitymentioning
confidence: 99%
“…Interest in modeling inter-regional connectivity has driven the development of new statistical techniques, as well as the application of established techniques from other fields [15*], including structural equation modeling, partial least squares, psychophysiological interactions and dynamic causal modeling. These techniques have demonstrated that functional interactions among brain areas are involved in a wide range of cognitive domains and correlate with performance, including cognitive control [16, 17], learning [18*], memory [19], attention [20], reward processing [21] and language [22]. Connectivity-based biofeedback studies have demonstrated that participants can be trained to self-regulate specific functional connections, resulting in desirable behavioral changes, such as increased subjective emotional valence ratings [23].…”
Section: From Regional Activations To Connectivitymentioning
confidence: 99%
“…Whilst the ways in which general activity of visual perception may, or may not, be exactly the same as the visual perception of specifi c piece of two-dimensional abstract art, such integrative activities are most surely similar. An example of perceptual complexity and integration is provided in a recent study that looked specifi cally at the handling by specialized neural regions in the processing of various orthographic aspects and semantic components of Chinese characters (Xu et al 2015 ). The authors cite how earlier neuroimaging studies into word recognition identifi ed functions within specifi c neural systems but that more recently studies have considered the integration and interaction of important aspects of distributed neural systems when considering visual word recognition (Xu et al 2015 ).…”
Section: Neuroscience and Visual Perceptionmentioning
confidence: 99%
“…An example of perceptual complexity and integration is provided in a recent study that looked specifi cally at the handling by specialized neural regions in the processing of various orthographic aspects and semantic components of Chinese characters (Xu et al 2015 ). The authors cite how earlier neuroimaging studies into word recognition identifi ed functions within specifi c neural systems but that more recently studies have considered the integration and interaction of important aspects of distributed neural systems when considering visual word recognition (Xu et al 2015 ). The authors suggest that this indicates the processing of languages that have an alphabet employ both the dorsal and ventral neural pathways that originate from the visual cortex.…”
Section: Neuroscience and Visual Perceptionmentioning
confidence: 99%
“…In the auditory domain, a large number of neuroimaging studies have revealed that lexical tone pro-cessing in speech is subserved by a bi-lateralized cortical network involving superior temporal regions, inferior prefrontal regions and the insula (Chang, Lee, Tzeng, & Kuo, 2014;Gandour et al, 2000;Hsieh, Gandour, Wong, & Hutchins, 2001;Klein, Zatorre, Milner, & Zhao, 2001;Kwok et al, 2016Kwok et al, , 2017Liang & Du, 2018;Liu, Peng, et al, 2006;Luo et al, 2006;Nan & Friederici, 2013;Ren, Yang, & Li, 2009;Schremm et al, 2018;Wong, Parsons, Martinez, & Diehl, 2004, Xi, Zhang, Shu, Zhang, & Li, 2010Yu, Wang, Li, & Li, 2014). Several studies have also illustrated left-lateralized connectivity network for lexical tone processing in speech (Ge et al, 2015;Xu, Wang, Chen, Fox, & Tan, 2015;Yang, Gates, Molenaar, & Li, 2015). In the visual domain, phonology has a role in activating word meanings in skilled silent reading (Coltheart, 2000;DeMarco, Wilson, Rising, Rapcsak, & Beeson, 2017;Jared, Levy, & Rayner, 1999;Ryherd et al, 2018;Tan & Perfetti, 1999), and thus, it is reasonable to postulate the contribution of lexical tone phonology to visual word recognition.…”
Section: Introductionmentioning
confidence: 99%